Panitumumab-Associated Encephalopathy after Accidental Intra-arterial Application through Dislocated Central Venous Access Device - Pikija, Slaven; Pilz, Georg; Gschwandtner, Gerald; Rösler, Cornelia; Schlick, Konstantin; Greil, Richard; Sellner, Johann (Frontiers in Neurology, 2016)
Acute central nervous system (CNS) toxicity and immune-related side effects are increasingly recognized with the use of monoclonal antibodies for cancer therapy. Here, we report a patient who developed of acute-onset encephalopathy and coma, which began shortly after administration of panitumumab for the treatment of metastatic colorectal cancer. Echocardiography revealed that the drug had been infused into the left cardiac ventricle via a dislocated central venous line. Diffusion-weighted magnetic resonance imaging disclosed multiple cortical hyperintensities, which were preferentially located in the frontal lobes. While the neurological condition improved within a few days, the patient died 4 weeks later. It seems likely that the administration of the antibody via the intra-arterial route contributed to the development of this condition. Toxic encephalopathy may be a hitherto unrecognized complication of panitumumab treatment and should be taken into consideration in patients developing CNS symptoms undergoing this therapy.